Dynamic integration and excision of filamentous phage XacF1 in Xanthomonas citri pv. citri, the causative agent of citrus canker disease. Issue 11 (19th September 2017) - Ahmad, Abdelmonim A.; Kawabe, Makoto; Askora, Ahmed; Kawasaki, Takeru; Fujie, Makoto; Yamada, Takashi
Abstract : Inovirus XacF1 (7325 nucleotides) is integrated into the genome of Xanthomonas citri pv. citri ( Xcc ) strains at the host dif site ( att B) by the host XerC/D recombination system. The XacF1 att P sequence is located within the coding region of ORF12, a possible phage regulator. After integration, this open reading frame (ORF) is split into two pieces on the host genome. We examined dynamic integration/excision of XacF1 in Xcc strain MAFF 301080 and found that the integration started at 4 h postinfection (p.i.) and peaked at 12 h p.i. Thereafter, the ratio of integrated to free forms remained constant, suggesting equilibrium of integration and excision of XacF1 in the host genome. However, the integrated state became very unstable following a 5′‐deletion of ORF12 in XacF1, suggesting that ORF12 plays a key role in the integration cycle of XacF1 in Xcc strains. Abstract : Inovirus XacF1 integrates into Xanthomonas citri pv. citri by XerC/D‐mediated recombination between phage ORF12‐ att P and att B ( dif ). After integration, ORF12 is split into two portions (ORF12′ and ORF12″) besides att L and att R. There is an equilibrium between integration and excision. The integrated state became very unstable following a 5′‐deletion of ORF12 in XacF1, suggesting that ORF12 plays a key role in the integration cycle.